Site selection for plastic recycling plant in a circular economy context using fuzzy decision-making system - Betul Yildirim (22675474) (2026)
Transitions to a circular and bioeconomy hinge not only on technologies but also on how waste infrastructures are spatially organized and socially negotiated. Yet, site selection for recycling facilities is often treated as a purely technical optimization, with limited attention to distributional effects, territorialization, and stakeholder arrangements. This study asks how a sustainability-oriented siting framework can make such socio-economic dynamics explicit while remaining analytically rigorous. We develop a hybrid multi-criteria decision-making approach that integrates Pythagorean Fuzzy Threshold-Based Attribute Ratio Analysis (PF-ITARA) for criteria weighting with Pythagorean Fuzzy Combinative Distance-based Assessment (PF-CODAS) for ranking alternatives, applied to five Turkish cities using expert judgments and sensitivity analysis. Results show the highest weights for setup cost, environmental contamination, natural hazards, occupational health hazards, and proximity to plastic waste sources, indicating that economic feasibility, risk, and social well-being jointly shape “where” circular systems materialize. İzmir and Kocaeli consistently top the rankings and function as functional hubs with market depth and multimodal access, whereas lower-ranked locations imply longer hauls, higher emissions, and potential drift back toward linear practices. The framework operationalizes transition priorities in a transparent, place-sensitive manner and offers actionable guidance for planners and regulators; future research should integrate dynamic waste-flow data, equity metrics, and scenario-based governance tests. Other Information Published in: Environmental Science & Policy License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.envsci.2026.104365